The definition of psychological aspects in the formation of student-centered motivation of students for classes in physical education - V.A. Gruzhevsky (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
An analysis of the publications, which demonstrates the importance of the emotional state in the formation of motivation as a psychological phenomenon. Shows the impact of physical education on the state of mental and emotional stress. Presented scientific analysis of psycho-emotional states in the 3rd year students with the region of residence and ethnicity. The study used survey results found that the circumstances are displayed on the psycho-emotional state of students. In their view, were: irritability, lack of confidence, fatigue, concern, guilt, etc. These conditions are more common in women of ethnic groups and from rural areas. It should be noted that the girls are very carefully described their emotional state and chose the answer in the questionnaire (sometimes), this response was dominant. Young men in many positions were more restrained. It is established that the formation of student-centered motivation of students to physical education should be adjusted in their emotional state. In this strategy the learning process of physical education is built on individual, ethnic differences.